Genetic analysis of downy and powdery mildew resistance in grapevine : a comparative study of 'Regent' and 'Red Globe' cultivars - Van Heerden, Carel Jacobus (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.